DETECTION OF SOME VIRULENCE, ANTIBACTERIAL RESISTANCE GENES FOR SALMONELLA ISOLATED FROM DOGS IN BAGHDAD CITY - Maher. S. Al – Rubaye,; Atheer. A. Al-doori, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Two hundred and fifty (250) samples from both diarrheic and non-diarrheic dogs in both sex male and female multi breeds ( German shepherd and malinois ) in Academy for training police and military dogs for searching about drugs , explosives ,local dogs and pet dogs from different clinical cases in Baghdad city were tested. All samples are obtained in aseptically rectal swabs and transporting to the microbiology lab, for culturing and identification for salmonella species. The study gave 16 (6.4%) positive Salmonella. Virulent gene study gave us 16(6.4%) invA gene, invF 13(5.2%) and sit C 16 (6.4%).Antibiotic sensitivity test According to Bauer-Kirby method were done and gave 16 (6.4%) isolates resistance for ciprofloxacin which is the most clinical antibiotic drug of choice against Salmonella infection . Detection of gyrA gene resistance gene for ciprofloxacin using Polymerase chain reaction (PCR) gave 16 (6.4%) for all positive isolates.